If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + -9h = 0 Solving -21 + -9h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -9h = 0 + 21 Combine like terms: -21 + 21 = 0 0 + -9h = 0 + 21 -9h = 0 + 21 Combine like terms: 0 + 21 = 21 -9h = 21 Divide each side by '-9'. h = -2.333333333 Simplifying h = -2.333333333
| (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 | | N-3=20/8 | | 6x+2=4-(2x-5) | | n^3-n^2=6n | | 4-5+7-4k=0 | | x+16=2x-24 | | 5t-3t=18+3(1-t) | | 2xy=x-3y | | 16-w=72 | | 7+3k-2=4 | | 3x-15=41-5x | | 5n+9-16+4=5(4n-2n+8) | | 0.5(4)^2^1/2 | | 2(n+1)+n=-4 |